Church and Society in the Past Century (1918–2018) - Miklós KOCSEV (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Honourable Participants! Ladies and Gentlemen! First of all, I would like to thank you for this wonderful opportunity to speak before you. I am grateful for this possibility, being fully aware that neither of the greeters knew what the others would say. And this is really not a problem as we are all different and we perceive the agenda of this two-day conference held in Kolozsvár/Cluj from different perspectives.